Interplay between colorectal cancer-related lifestyles and the gut microbiome: an exploratory analysis of metagenomic data - Rilla Tammi; Mirkka Maukonen; Niina E. Kaartinen; Kari Koponen; Teemu Niiranen; Guillaume Méric; Demetrius Albanes; Johan G. Eriksson; Pekka Jousilahti; Seppo Koskinen; Anne-Maria Pajari; Rob Knight; et al. (Cancer Causes & Control, 2026)
Purpose The gut microbiome may modify the associations between lifestyle factors and colorectal cancer (CRC) risk, but their complex interplay, including the interactions between lifestyle factors, remain underexplored. We examined associations between CRC-related lifestyle patterns and gut microbiome diversity and composition in Finnish adults. Methods Our data included 1,228 adults aged 25–64 years from the National FINRISK/FINDIET 2002 Study. Information on lifestyle and background factors was obtained through self-administered questionnaires. Dietary data were gathered using a 48-h dietary recall. CRC-related lifestyles were modelled using a CRC lifestyle index based on nine major risk factors for CRC. Lower index points reflected higher-risk lifestyles. The gut microbiome profiles were analyzed using shallow shotgun metagenome sequencing. Associations between the index and microbial diversity and composition were assessed using, e.g., linear regression and permutational multivariate ANOVA adjusted for relevant confounders. Results The index explained 0.2% of the variation in microbial composition between participants ( p < 0.05). Higher-risk lifestyles for CRC were associated with lower microbial diversity ( β 0.037, p 0.009). Higher-risk lifestyles were also associated with a higher relative abundance of species representing primarily the family Lachnospiraceae and genera such as Dorea and Mediterraneibacter , and lower relative abundance of species within the genus Bifidobacterium (< 0.0001). Conclusions Participants with higher- and lower-risk lifestyles showed clear differences in their gut microbiome diversity and composition, higher-risk lifestyles being associated with potentially adverse microbial traits. These findings contribute to identifying microbial features that may characterize early stages of CRC development in individuals with high-risk lifestyles.